Protective Effects and Mechanisms of Rosuvastatin on Acute Kidney Injury Induced by Contrast Media in Rats - Zehui Jiang; Jun Zhang; Yuanan Lu (International Journal of Nephrology)
Objective. To explore the protective effect and mechanism of rosuvastatin on acute renal injury induced by a nonionic hypotonic contrast medium in rats. Methods. Forty-eight healthy adult SD rats were randomly divided into three groups: normal control group (NC); contrast medium control group (CM); and rosuvastatin intervention group (RI). The RI group was intragastrically administered with a 10 mg/kg of rosuvastatin 12 h prior to the contrast exposure. All rats in CM and RI groups were inoculated with 10 mL/kg of chemical (IV) while the same volume of saline for the NC group. At 24 h and 72 h posttreatments, pathomorphological changes of renal tubules were documented, respectively, and several biochemical indicators were tested to assess renal injury of experimental rats. Results. Compared with the CM group, rats in the RI group showed significantly reduced injury of kidneys and decreased levels of biochemical indicators such as blood Scr, blood Cys-C, urine NAG, urine α1-MG, and urine mALB. The serum Hs-CRP in the CM group increased significantly from 24 h to 72 h (p<0.05), but this was not observed in the rats of the RI group. In addition, SOD activity in the RI group was significantly increased (p<0.01) while SOD activity in renal tissue decreased significantly with time in the CM group (p<0.05). Conclusion. Short-term intervention with rosuvastatin can lead to reduced kidney damage associated with the contrast agent by reducing the levels of inflammatory factors and oxidative stress. Thus, rosuvastatin intervention has a protective effect on rats from contrast-induced nephropathy.